2000
DOI: 10.1152/ajpcell.2000.279.6.c1870
|View full text |Cite
|
Sign up to set email alerts
|

Guanine nucleotide transport by atractyloside-sensitive and -insensitive carriers in isolated heart mitochondria

Abstract: In previous work (McKee EE, Bentley AT, Smith RM Jr, and Ciaccio CE, Biochem Biophys Res Commun 257: 466-472, 1999), the transport of guanine nucleotides into the matrix of intact isolated heart mitochondria was demonstrated. In this study, the time course and mechanisms of guanine nucleotide transport are characterized. Two distinct mechanisms of transport were found to be capable of moving guanine nucleotides across the inner membrane. The first carrier was saturable, displayed temperature dependence, prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…However, in mammalian cells, other members of the carrier family could carry out the transport of GTP or GDP. For example, isolated rat heart mitochondria have been reported to transport guanine nucleotides, and two distinct transport mechanisms have been identified [7,27,28]. The targeting of a human NDPK (Nm23-H4) to the mitochondrial matrix of ggc1 rescues the iron phenotypic defects of the yeast mutant.…”
Section: Resultsmentioning
confidence: 99%
“…However, in mammalian cells, other members of the carrier family could carry out the transport of GTP or GDP. For example, isolated rat heart mitochondria have been reported to transport guanine nucleotides, and two distinct transport mechanisms have been identified [7,27,28]. The targeting of a human NDPK (Nm23-H4) to the mitochondrial matrix of ggc1 rescues the iron phenotypic defects of the yeast mutant.…”
Section: Resultsmentioning
confidence: 99%
“…The intracellular location of the different isoforms of this enzyme in muscle is not clear, although studies suggest that hepatic nucleoside diphosphokinase is present outside the mitochondrial matrix. There is also evidence that GTP may be transported directly from the mitochondrial matrix on an atractyloside-insensitive carrier, but the rate of transport via this carrier is slower than the well characterized ATP/ADP translocase (23). However, the requirement for guanine nucleotides in non-dividing tissues is low, so that the transport process may be sufficient to meet the physiological requirements for guanine nucleotides in tissues such as skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…GTP salvage inside the matrix is critical because it is believed not to be transported through the inner mitochondrial membrane in higher organisms (Pfaff et al 1965). However, guanine nucleotide transport by atractyloside-sensitive and -insensitive mechanisms in isolated heart mitochondria has been reported by one group (McKee et al 1999(McKee et al , 2000, but the carrier has not been found. On the other hand, it is well established that yeasts harbor a mitochondrial GTP/GDP translocase, but a homologue in higher organisms has not been identified (Vozza et al 2004); accordingly, yeasts lack a GTPforming SUCL (Przybyla-Zawislak et al 1998).…”
Section: Introductionmentioning
confidence: 95%